Gene ilvY of Salmonella typhimurium. - Blazey, D L (1980)
Evidence is presented for the existence in Salmonella typhimurium LT2 of the regulatory gene ilv Y. The Escherichia coli K-12 ilvY gene product is shown to complement a S. typhimurium ilvY mutation in vivo.